Ethylene Signal Is Involved in the Regulation of Anthocyanin Accumulation in Flesh of Postharvest Plums (Prunus salicina Lindl.) - Xueling Li; Yudou Cheng; Ying Wang; Xiaohe Yang; Chuangqi Wei; Junfeng Guan (Plants, 2023)
Ethylene is positively correlated with the anthocyanin accumulation in postharvest plum fruit, but the regulation mechanism has not been fully clarified. In this work, the ‘Friar’ plum fruit under different storage temperatures (0, 10 and 25 °C) and treatments (100.0 μL L−1 ethylene and 1.0 μL L−1 1-MCP) were applied to study the relationship between anthocyanin accumulation and ethylene signal pathway. The fruits stored at 10 °C had higher ethylene production rate and more anthocyanin in flesh than those stored at 0 °C and 25 °C. Ten ethylene biosynthesis associated genes and forty-one ethylene signal transduction related genes were obtained from the previous transcriptome data. Among them, the expression levels of ethylene biosynthesis associated genes (PsACS1, PsACS4 and PsACO1), and ethylene signal transduction related genes (PsERS1s, PsETR2, PsERF1a, and PsERF12) were markedly higher in the fruits stored at 10 °C than those at 0 °C and 25 °C. Exogenous ethylene treatment enhanced while 1-MCP treatment inhibited the anthocyanin accumulation in the flesh under storage at 10 °C. In addition, exogenous ethylene treatment markedly increased the expression levels of PsACS1, PsACS4, PsACO1, PsETR2, PsERF1a, and PsERF12 in the flesh once it turning red, as well as the anthocyanin biosynthesis related genes (PsPAL, PsCHS, PsF3H, PsDRF, PsANS, PsUFGT and PsMYB10), whereas 1-MCP treatment manifested the contrary effects. Correlation analysis indicated that there was a significant positive correlation between genes expression related to ethylene signal pathway and anthocyanin biosynthesis, except for PsERF11. In conclusion, ethylene signal pathway is involved in the flesh reddening by up-regulating the anthocyanin biosynthesis related genes.